2022
DOI: 10.5198/jtlu.2022.1879
|View full text |Cite
|
Sign up to set email alerts
|

Whose express access? Assessing the equity implications of bus express routes in Montreal, Canada

Abstract: Express buses—characterized by limited stops and sometimes higher frequencies or priority traffic measures—offer a cost-effective and efficient way to boost service convenience and reliability for riders. This paper assesses how the accessibility benefits of express bus route policy are distributed in Montreal, Canada, while providing a pathway for public transportation agencies to assess their policies and plans. To isolate the impact of bus express routes, we use General Transit Speed Specification (GTFS) da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This includes characteristics such as population and employment density (Frank & Pivo, 1994), airline distance from public transit for home based trip to work (Lee et al, 2014) and distance from CBD for home and work location (Ding et al, 2018). Whereas most studies focus solely on the home location, and to a lower extent, work location, this study highlights the relevance of jointly considering the variety of factors that determine future usage as highlighted in previous study (DeWeese et al, 2022;Frank & Pivo, 1994;Larsen et al, 2009). Indeed, as observed through the results of the logistic regression models, characteristics of the home and work location interact with one another: living in a suburban area while working in the CBD (the typical commuters) does not have the same implications as living and working in a suburban area (the suburbanites).…”
Section: Discussionmentioning
confidence: 68%
“…This includes characteristics such as population and employment density (Frank & Pivo, 1994), airline distance from public transit for home based trip to work (Lee et al, 2014) and distance from CBD for home and work location (Ding et al, 2018). Whereas most studies focus solely on the home location, and to a lower extent, work location, this study highlights the relevance of jointly considering the variety of factors that determine future usage as highlighted in previous study (DeWeese et al, 2022;Frank & Pivo, 1994;Larsen et al, 2009). Indeed, as observed through the results of the logistic regression models, characteristics of the home and work location interact with one another: living in a suburban area while working in the CBD (the typical commuters) does not have the same implications as living and working in a suburban area (the suburbanites).…”
Section: Discussionmentioning
confidence: 68%
“…Elliott and Lumley [9] proposed a travel time model based on GTFS and GPS vehicle locations, which is a wonderful way to make time prediction of bus in actual practice if GPS location is available. Moreover, the paper on the model for planning limited-stop transit operations proposed by Nesheli, Srikukenthiran, Shalaby [5] and bus express mode evaluation declared by DeWeese et al [4] are also based on GTFS. These increasingly GTFS-based study has revealed the reliability and value of GTFS.…”
Section: Related Workmentioning
confidence: 99%
“…Different from the limitation on metro lines, for instance, the need for extra tracks and the restriction on overtaking [3], city bus has more degrees of freedom. According to DeWeese et al [4], express routes mode could significantly contribute to society, including reducing commuting time and improving the employment environment. Furthermore, a preferable way to reduce public resource waste and increase utilization is to skip some unimportant stops for each bus line [5].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond these environmental and economic goals, LRT projects should also strive to foster equitable transport systems, which means ensuring that the social and economic benefits of major infrastructure investments are fairly distributed across society ( 47 ). There are major gaps, however, in knowledge about how these public-transit investments serve the wants and needs of different segments of society, particularly with regards to LRT and gender ( 8 ).…”
mentioning
confidence: 99%